Ring-shaped meniscus formation may arise from the regenerative response to meniscectomy during growth spurts: A case report. (2019) - Nagashima, Masaki; Otani, Toshiro; Kojima, Kota; Aida, Shinsuke; Ishii, Ken
Highlights: We presented a case of newly formed ring-shaped meniscus-like tissue after partial resection of discoid lateral meniscus. The newly formed interhorn bridge could have represented a meniscus-like tissue that appeared secondary to tissue repair. Intra-patient findings indicate that growth spurts may promote the tissue repair. Abstract: Introduction: Ring-shaped meniscus is very rare and generally considered to be a congenital malformation. Here, we report a case of newly formed ring-shaped meniscus-like tissue following arthroscopic partial meniscectomy for a complete discoid lateral meniscus. Presentation of case: A 14-year-old boy underwent arthroscopic partial meniscectomy for complete discoid lateral meniscus of the left knee. The growth plates were present at the surgery. Although pain improved immediately after surgery, he reported left knee pain at the 7-month follow-up. Magnetic resonance imaging revealed a bucket-handle tear of the lateral meniscus and a second arthroscopic surgery was performed. During arthroscopy, we found that the anterior and posterior horns of the lateral meniscus were connected by meniscus-like tissue forming a ring-shaped meniscus and the newly formed interhorn meniscal bridge was resected. Histological evaluation indicated that the newly formed tissue was meniscus-like tissue that had appeared secondary to tissue repair. He visited our hospital at 16 years old, after the growth plates had closed, complaining of right knee pain. Arthroscopic partial meniscectomy was performed for complete discoid lateral meniscus of the right knee. As of two years after this surgery, no morphological changes have been observed. Discussion: Although the exact mechanisms of meniscus-like tissue formation remain unclear, the growth spurt may promote the mechanisms of tissue repair, forming ring-shaped meniscus-like tissue. Conclusion: This is the first case of ring-shaped meniscus-like tissue forming after partial resection of a complete discoid lateral meniscus. Ring-shaped meniscus-like tissue can develop in growing patients.